2016
DOI: 10.1038/cddiscovery.2015.70
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the ectopically expressed olfactory receptor 2AT4 in human myelogenous leukemia

Abstract: The olfactory receptor (OR) family was found to be expressed mainly in the nasal epithelium. In the last two decades members of the OR family were detected to be functional expressed in different parts of the human body such as in liver, prostate or intestine cancer cells. Here, we detected the expression of several ORs in the human chronic myelogenous leukemia (CML) cell line K562 and in white blood cells of clinically diagnosed acute myeloid leukemia (AML) patients by RT-PCR and next-generation sequencing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 48 publications
1
70
1
Order By: Relevance
“…Despite our current data demonstrating an oncogenic function for ORs, several studies have suggested that ORs may act as tumour suppressors24565758. The activation of OR2AT4 and OR51B5 in myelogenous leukaemia K562 cells, decreased proliferation and enhanced apoptosis and differentiation5657.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Despite our current data demonstrating an oncogenic function for ORs, several studies have suggested that ORs may act as tumour suppressors24565758. The activation of OR2AT4 and OR51B5 in myelogenous leukaemia K562 cells, decreased proliferation and enhanced apoptosis and differentiation5657.…”
Section: Discussioncontrasting
confidence: 55%
“…The activation of OR2AT4 and OR51B5 in myelogenous leukaemia K562 cells, decreased proliferation and enhanced apoptosis and differentiation5657. In addition, activation of OR51E1 in prostate cancer cells suppressed cell proliferation2458.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have served as a basis for functional studies that demonstrate the potential of the ORs as drug targets (Neuhaus et al, 2009; Busse et al, 2014; Maßberg et al, 2015; Manteniotis et al, 2016a,b; Tsai et al, 2016). In this study, for the first time, we describe the expression of the OR mRNAs and the localization of the OR proteins in the mature human retina.…”
Section: Discussionmentioning
confidence: 96%
“…OR2AT4 is another example of the therapeutic potential of ORs in human skin because its activation promotes wound healing processes in human keratinocytes (Busse et al, 2014). They are also of major importance for the regulation of apoptosis, cytokinesis, hormone secretion and differentiation (Braun et al, 2007; Zhang et al, 2012; Maßberg et al, 2015; Gelis et al, 2016; Manteniotis et al, 2016a,b; Massberg et al, 2016; Tsai et al, 2016). However, the expression and localization of ORs in different areas of the brain, the spinal cord, the trigeminal (TG) and dorsal root ganglia (DRG) were recently described (Otaki et al, 2004; Garcia-Esparcia et al, 2013; Flegel et al, 2015; Goncalves et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ORs came into the focus of drug development because ectopically expressed ORs were involved in physiological and pathophysiological mechanisms within human tissues, such as the chemotaxis of sperm, the proliferation of prostate cancer and liver cancer cells, the induction of wound-healing, the modulation of hepatic triglyceride metabolism, cytokinesis, apoptosis and the regulation of serotonin secretion [8, 13, 58, 60, 67, 79, 82, 90, 99, 108, 114]. …”
Section: Introductionmentioning
confidence: 99%